Knowledge about own memory in patients with dementia of the Alzheimer type - preliminary study - Szepietowska, Ewa Małgorzata (Studia Psychologica: Theoria et praxis, 2011)
Most of the data obtained from studies of memory in patients with dementia, especially with the dementia of Alzheimer type indicates unawareness of deficits of their own memory. The results of previous research are not consistent, however, suggest that certain aspects of patients’memory can be adequately assessed by them. The research involved patients with DAT (N=15) and appropriately selected group of individuals without neuropsychiatric diseases (N=15). The task was estimate the level of recall of words from the list (judgment of learning - 10 trials), and then to remember and recall those words (10 trials). The subjective (estimates) and objective (level of reminding) results were compared. During studies the level of intensity of depression, the overall level of cognitive functioning and language capabilities and the subjective assessment of general characteristics of own memory and their correlation with the level of estimation and recall of lists of words was analyses. It was found that the DAT patients had stayed below their possibilities to remember words, and recalled fewer words than control group. Both patients with DAT and healthy individuals overestimated their own skills. In the control group the relationship between the intensity of depressive mood, general assessment of their own memory, overall level of cognitive functioning and the subjective assessment of the possibilities to remember a list of words, and sometimes also with the level of reminders was demonstrated. None of these variables (general assessment of own memory, language capabilities, overall level of cognitive functioning) did not specifically affected subjective ratings and performances in DAT group. Data suggest, that not all aspects of knowledge about own memory disintegrate in DAT. In dementia the knowledge about general properties of memory and about its specific aspects became independent processes which that in healthy subject are mutually dependent.